2011
DOI: 10.3944/aott.2011.2481
|View full text |Cite
|
Sign up to set email alerts
|

The advantages of computer assistance in total knee arthroplasty

Abstract: Our results suggested that computer assistance provides a more accurate alignment in TKA. The reduced incision length and hospitalization time appear as two other advantages of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…CAS significantly improves varus/valgus angle [15,17-20,47], mLDFA [16,17,21-23], mMPTA [16,17,20,21,23], femoral flexion angle [15,16,18,21,22], tibial downslope [15,18,20,22,23] and rotational alignment for the femoral and tibial components [15,16,20]. Perlick et al [25] revealed a significantly better mechanical limb axis and coronal alignment of the femoral component when CAS was used during rTKA.…”
Section: Discussionmentioning
confidence: 99%
“…CAS significantly improves varus/valgus angle [15,17-20,47], mLDFA [16,17,21-23], mMPTA [16,17,20,21,23], femoral flexion angle [15,16,18,21,22], tibial downslope [15,18,20,22,23] and rotational alignment for the femoral and tibial components [15,16,20]. Perlick et al [25] revealed a significantly better mechanical limb axis and coronal alignment of the femoral component when CAS was used during rTKA.…”
Section: Discussionmentioning
confidence: 99%